Pengaruh Kualitas Pelayanan dan Kualitas Produk terhadap Kepuasan Konsumen Pada Waroeng Spesial Sambal Lippo Karawaci - Aris Ariyanto; Anisah Anisah; Umi Narimawati (Mahesa Research Center, 2022)
The purpose of this study was to determine the effect of service quality and product quality on consumer satisfaction at Waroeng Special Sambal in Lippo Karawaci Tangerang, either partially or simultaneously. The method used is quantitative. The sampling technique used the Slovin formula and the sample in this study was 100 respondents. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of this study are the quality of service has a significant effect on customer satisfaction with a coefficient of determination of 45.5%. Hypothesis test obtained t arithmetic > t table or (9.051 > 1.984). Product quality has a significant effect on consumer satisfaction with a coefficient of determination of 44.7%. Hypothesis test obtained t count > t table or (8,902 > 1,984). Service quality and product quality simultaneously have a significant effect on customer satisfaction with the regression equation Y = 10,473 + 0.363X1 + 0.382X2. The value of the coefficient of determination is 54.5% and the hypothesis test is obtained by the calculated F value > F table or (58,155 > 2,700).